Pumpless microfluidic system driven by hydrostatic pressure induces and maintains mouse spermatogenesis in vitro - Komeya, Mitsuru (Sci Rep, 2017)
Three-dimensional aggregation and organ culture methods are critical for recreating in vivo cellular phenomena outside the body. Previously, we used the conventional gas liquid interphase organ culture method to induce complete mouse spermatogenesis. After incorporating microfluidic systems, we achieved a significant increase in efficiency and duration of spermatogenesis. One of the major drawbacks preventing the popularization of microfluidics, however, is the use of a power-pump to generate medium flow. In this study, we produced a pumpless microfluidic device using hydrostatic pressure and a resistance circuit to facilitate slow, longer lasting medium flow. During three months of culture, results in induction and maintenance of spermatogenesis showed no difference between pumpless and pump-driven devices. Correspondingly, the spermatogonial population was favorably maintained in the pumpless device compared to the conventional method. These results show the advantage of using microfluidic systems for organ culture experiments. Our pumpless device could be applied to a variety of other tissues and organs, and may revolutionize organ culture methods as a whole.